Role of aqueous extract of Crocus sativus to improvement of sexual dysfunctions induced by imipramine in male mice - Askar, Salma J. (The Iraqi Journal of Veterinary Medicine, 2017)
The present study was carried out to focus light on the possible improvement and enhancement of functional performance of male mice sexual activities by using the aqueous extract of Crocus sativus. Several pharmaceutical drugs affect sexual activities and upset the sexual desire sequence that can lead to impotence or loss libido, example of these drugs are tricyclic antidepressant such as imipramine. To achieve this goal, twenty adult albino male mice were used, which were randomly divided into equal four experimental groups. The first group was given 10 mg/kg B.W. imipramine, the second group was given 100 mg/kg B.W. aqueous extract of Crocus sativus, and the third group was given 100 mg/ kg B.W. Crocus sativus aqueous extract and 10 mg/ kg B.W. imipramine, while the fourth group served as control, which was given D.W. In all groups the doses were given orally by stomach tube at 0.1 ml/10 g. B.W. for 30 days. The recorded parameters were; latency of copulation (second), frequency of copulation (per-hour), and duration of copulation (second). At day thirty blood samples were collected to determine the hormonal levels of luteinizing and testosterone hormones and the testis were obtained for histopathological processing .The results of sexual activity measured parameters showed significant decrease (P<0.05) in latency of copulation and significant increase in both frequency of copulation, and duration of copulation in the groups given aqueous extract of Crocus sativus and that given aqueous extract of Crocus sativus and imipramine as compared with imipramine and control groups. While results of hormonal levels showed significant increase (P<0.05) in both groups of Crocus sativus aqueous extract and imipramine as compared with imipramine only and control groups. On bases of these results, it can be concluded that the sexual activities of male mice given imipramine tend to be improved and returned when administered with aqueous extract of Crocus sativus.